The network effect: studying COVID-19 pathology with the Human Cell Atlas - Teichmann, Sarah (Nat Rev Mol Cell Biol, 2020)
The SARS coronavirus 2 (SARS-CoV-2) pandemic is a global challenge, which the scientific community has tackled by mounting extensive global collaborations, combining expertise in diverse areas and applying cutting-edge techniques, to dissect mechanisms underlying coronavirus disease-19 (COVID-19) pathology. The Human Cell Atlas consortium is emerging as an important contributor to furthering this progress.